Dialogic feedback as divergent assessment for learning: an ecological approach to teacher professional development. Issue 3 (1st September 2016) - Charteris, Jennifer
Abstract : Neoliberal policy objectives perpetuate an audit culture at both school and system levels. The associated focus on performativity and accountability can result in reductive and procedural interpretations of classroom assessment for learning (AfL) practices. Set in a New Zealand AfL professional development context, this research takes an ecological view of teacher learning as a ground-up approach to improving practice. As a framework, this paper brings together an intersubjective conception of professional learning that positions teachers as co-leaders, principles inherent in 'the spirit of AfL', and the notion of 'intelligent accountability' to illustrate evidence-informed teacher agency. It applies divergent and dialogic AfL practices to professional learning that can enable teachers to connect with issues that are most relevant to their practice. Dialogic feedback practices of this nature position teachers as capable, reflexive and resourceful practitioners and decision-makers.